A parametric study on the impact of integrating solar cell panel at building envelope on its power, energy consumption, comfort conditions, and CO2 emissions. (10th March 2020) - Elghamry, Rania; Hassan, Hamdy; Hawwash, A.A.
Abstract: This paper presents a parametric study on the impact of solar cells at the building envelope on the generated power, energy consumption, comfort conditions (interior temperature, relative humidity, discomfort hours, and lighting), and CO2 emissions within a building. It considers the cell position on the facade (cell inside window, two cells outside the window), orientation direction (north, east, south, west), and location (wall, roof). The study is performed under the meteorological conditions in the city of New Borg El Arab, Alexandria, Egypt. The numerical solution of the physical model is solved using the Design-Builder software and is validated through an experiment. The results reveal that solar cells on the facade and roof decrease the annual energy consumption inside the facility by approximately 15% and 40%, respectively, compared to a facility without cells. A cell installed on the roof facing south has the highest annual generated power. For a solar cell on the wall, a cell facing south produces the highest annual generated power and a cell facing north produces the lowest. The temperature inside the facility is lower when the solar cells are installed, and a cell facing south provides comfortable interior conditions in all the investigated cases. A cell located inside the window produces the lowest light intensity and a cell facing north produces the lowest CO2 emissions. Highlights: Solar cell at south wall produces maximum annual cell power generation while north produces the minimum. Installed solar cell in the facade decreases the annual energy consumption inside the building by 15%. Solar cell locates inside the window has the minimum light intensity compared to other positions. Temperature inside building for all cell cases is lower than the temperature in case of not use cell. Building with cell oriented to north produces minimum annual CO2 emission in the building.